PERAN CITRA MEREK MEMEDIASI PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN - Arlis Chintya, Paulina Kinpika; Gde Sukaatmadja, I Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.05.TAHUN.2024, 2024)
This study aims to explain the role of brand image in mediating product quality and service quality on purchasing decisions. This study uses a non-probability sampling method with the criteria of respondents living in Denpasar City. The data analysis technique used is path analysis and Sobel test with SPSS program. The study was conducted in Denpasar City with a sample size of 140 respondents. Product quality has a positive and significant effect on purchasing decisions, service quality has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on brand image, service quality has a positive and significant effect on brand image, brand image has a positive and significant effect on purchasing decisions, brand image is able to fully mediate the influence of product quality on purchasing decisions and brand image is able to significantly mediate the influence of service quality on purchasing decisions. The implications of product quality and service quality affect purchasing decisions, thus product quality and service quality have a positive and significant effect on purchasing decisions. Brand image has a significant positive effect on purchasing decisions.